Psychogenic hearing loss in children and adolescents. Diagnosis and psychotherapy - Grażyna Gwizda; Anna Horaczyńska-Wojtaś; Grażyna Mielnik-Niedzielska; Anna Kasprzyk; Lechosław Paweł Chmielik; Artur Niedzielski (Annals of Medicine)
Introduction Psychogenic hearing loss is often neglected in the differential diagnosis of hearing disorders. In a difficult diagnostic process and treatment of psychogenic hearing loss disorder, the close cooperation of the audiologist, psychologist, patient, and his family is required. The study aimed to improve the knowledge and understanding of psychogenic hearing loss, establish a differential diagnosis in audiological tests in children, determine diagnostic procedures and finally apply adequate therapeutic procedures. The professional knowledge presented in the study will enable adaptation of reliable information which can be transferred to young patients and their families to let them recognize their problems.Material and methods A group of 321 children, admitted to the Department of Pediatric Otorhinolaryngology, Phoniatrics and Audiology, The Children’s Hospital in Lublin, Poland, from January 2019 to December 2021, who complained of hearing loss were analysed in the study.Results Twenty-two patients (15 girls and 7 boys) met the audiological criteria of psychogenic hearing loss and were enrolled to the study. Seventeen children complained of bilateral hearing loss, and five patients presented with a unilateral hearing loss.Conclusions Family and personality problems cause unresolved difficulties in children and can lead to psychogenic deafness. Constant interest demonstrated by a guardian not only when the child is causing troubles or is complaining of disease is the key to avoiding developing psychosomatic disorders such as psychogenic hearing loss.